“Just Wear It, Stay Safe”: A Critical Discourse Analysis of Sexually Transmitted Infection Prevention Campaigns in Public Health Communication - Chutintaranond, Thanasin (Thammasat Journal, 2026)
This academic article aims to examine the state-led public health communication concerning the prevention of sexually transmitted infections (STIs) through the lens of Critical Discourse Analysis, specifically employing Fairclough’s dialectical-relational approach. The analysis is conducted across three levels: text, discourse practice, and socio-cultural practice, integrating perspectives from the field of communication studies. The study finds that the discourse “Just Wear It, Stay Safe” reflects deeper issues within Thailand’s sexual education ecosystem. Although the state exercises its authority to disseminate knowledge to the public, the promotional materials used may contribute to public misconceptions regarding STI prevention. Furthermore, state communication about condom use does not fully align with the definitions articulated in the National Condom Strategy and reveals significant limitations in public awareness and accessibility to female condoms in Thai society. The findings also highlight a gendered imbalance, wherein the responsibility for safe sex practices is disproportionately assigned to men. Therefore, the study calls for a structural re-evaluation of sexual education discourse in Thailand, advocating for a tripartite collaboration among governmental agencies, higher education institutions, and the family unit to ensure a more inclusive, equitable, and effective approach to sexual health communication.